STANDARD MBTHOD OF RMSE CALCULATION FROM POLYNOMIAL RECTIFICATION (Journal of Engineering, 2002)
Image quality and geometric accuracy of SPOT data are essential elements in cartographi: applications. The evaluation of geometric accuracy of SPOT data is carried out by analysis and quantification of the errors in geometric correction. For this purpose, many programs are designed to correct the image geometrically (polynomial transformation) and to calculate the root mea 1 square error (RMSE) by the standard method.The standard method of calculating the RMSE is shown to be capable of providing accurate estimates of geometric error when a modest number of control points is available (between 10-15 points). This method also provides an indication of the effects of choosing differer t polynomial orders.